Bone Quality Obtained in Sinus Lifting with Anorganic Bovine Bone. A CBCT Study - Martínez Soledad Melisa; Ibañez Maria Constanza; Ibañez Juan Carlos (International Journal of Oral and Craniofacial Science - Peertechz Publications, 2020)
Objective: Quantitatively assess bone density in maxillary sinus lifting with ABB (Bio-Oss®), using Cone-Beam computed tomography 6 months after surgery. Material and methods: A retrospective observational study was conducted between February 2018 and February 2019 on 33 Cone-Beam tomographic studies of 29 adult patients of both genders, with maxillary sinus floor lift, using Bio-Oss® small particles ( 0.25-1um), large particles (1-2um) or a 50-50 % mix of both, always using Bio-Gide® membranes, in order to measure bone density through Hounsfield Units (UH) after 6 months of healing.  Results: The average density of the grafted sinuses was 586 ± 238 HU, corresponding to Type II-III bone. Gender (p = 0.079) and Residual bone (p = 0.681) showed no significant differences, while Age (p = 0.015) and Particles Size (p = 0.002; p <0.05), were significant. The highest tomographic density was obtained in patients older than 65 years; and in mixed particles size grafts. Conclusion: The bone density obtained after maxillary sinus lifting with Bio-Oss shows quantitative ​​values similar to those of type II-III bone, providing a high degree of predictability for implant placement 6 months after the intervention.